Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex]\text{Given that,}\\\\2(x^2+y^2)^2 = 25 (x^2-y^2)\\\\\implies 2\dfrac{d}{dx} (x^2 +y^2)^2 = 25 \dfrac{d}{dx} (x^2 -y^2)\\\\\implies 2 \cdot 2(x^2 +y^2) \dfrac{d}{dx}(x^2 +y^2) = 25\left[2x - 2y \dfrac{dy}{dx} \right]\\\\\implies (4x^2 +4y^2)\left(2x + 2y\dfrac{dy}{dx}\right) = 50x - 50y\dfrac{dy}{dx}\\\\\\\implies 8x^3+8x^2y \dfrac{dy}{dx} + 8xy^2 +8y^3\dfrac{dy}{dx} = 50x -50y \dfrac{dy}{dx}\\\\\\\implies 8x^2y \dfrac{dy}{dx} + 8y^3\dfrac{dy}{dx}+50y \dfrac{dy}{dx} = 50x -8x^3 -8xy^2\\\\[/tex]
[tex]\implies (8x^2y +8y^3 + 50y)\dfrac{dy}{dx} =50x -8x^3 -8xy^2\\\\\implies \dfrac{dy}{dx} = \dfrac{50x -8x^3 -8xy^2}{8x^2y+8y^3+50y}\\\\\implies \dfrac{dy}{dx}= \dfrac{25x-4x^3-4xy^2}{4x^2y+4y^3+25y}\\\\\\\implies \dfrac{dy}{dx} = \dfrac{x(25-4x^2-4y^2)}{y(4x^2 +4y^2 +25)}\\\\\\\text{Slope at}~~ (-3,-1)\\\\m=\dfrac{dy}{dx} = \dfrac{-3[25-4(-3)^2-4(-1)^2]}{(-1)[4(-3)^2 + 4(-1)^2+25]} = -\dfrac{45}{65} = -\dfrac 9{13}[/tex]
[tex]\text{Equation with given points,}\\\\y+1 = -\dfrac9{13}(x+3)\\\\\implies y = -\dfrac 9{13} x - \dfrac {27}{13} -1\\\\\implies y= -\dfrac 9{13} x - \dfrac{40}{13}\\\\\text{Hence the equation of this tangent line is now in a form of y= mx+b,}\\\\\text{where}~ m = -\dfrac 9{13}~ \text{and}~ b = -\dfrac{40}3[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.